Kinetic Evaluation of Fixed Film Fixed Bed Anaerobic Reactor by Using Dairy WasteWater - Ramesh, T (International Journal of Pharmaceutical & Biological Archive, 2012)
Kinetic Evaluation of Fixed Film Fixed Bed Anaerobic Reactor by Using Dairy WasteWater